Heavy Metal and Selected Water Quality Parameters in Santubong Bay and Salak Island - Fatin Khairunnisa, Zaimi (Universiti Malaysia Sarawak(UNIMAS), 2015)
This study was conducted to know the current status of the estuarine and coastal areas of Salak river as comparison to previous study and Santubong bay for aquatic organisms especially toward Irrawady dolphin which is found populating the areas. The objectives of this study are to determine the concentration of selected heavy metals such as Lead (Pb), Nickel (Ni), Chromium (Cr), Cadmium (Cd), Zinc (Zn), Copper (Cu), Manganese (Mn), Mercury (Hg); and to determine the selected water quality parameters. The result showed the concentration of metals in Salak River and Santubong coastal areas varies through sampling locations; the concentration range fir Zn is (0.0346 mg/L-0.0686 mg/L), Cr (0.0241 mg/L- 0.0859 mg/L), Pb (0.0171 mg/L- 0.0498 mg/L), Mn (0.0043 mg/L- 0.0175 mg/L), Hg (0.0080 μg/L- 0.0480 μg/L), while Ni, Cd and Cu are below detection limit of FAAS (Flame Atomic Adsorption Spectrometer). Zn, Cr and Pb concentrations exceed Marine Water Quality Criteria and Standard from the Department of Environmental Malaysia (DOE) and Word Health Organization (WHO). The selected water quality parameters were collected during the sampling day in the occurrence of high tide.